2007
DOI: 10.1242/jeb.002949
|View full text |Cite
|
Sign up to set email alerts
|

Multiple modulators act on the cardiac ganglion of the crab,Cancer borealis

Abstract: crustacean cardioactive peptide (CCAP), a number of extended FLRFamide peptides, and cholinergic agonists increased the activity of the CG, GABA inhibited the CG, while other substances had little or no significant effect on the CG motor pattern. These results demonstrate, in one species, that the CG is multiply modulated. We suggest that multiple modulators may be important to regulate and coordinate the activity of the heart and other organs in response to external stimuli or the endogenous physiological sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 102 publications
4
72
0
2
Order By: Relevance
“…Mercier and Russenes, 1992;Wilkens et al, 2005;Cruz-Bermúdez et al, 2006;Cruz-Bermúdez and Marder, 2007;Dickinson et al, 2007;Fort et al, 2007a;Fort et al, 2007b;Christie et al, 2008b;Dickinson et al, 2009). As described earlier, one H. americanus tissue in which CLDH message was detected is the CG, which controls the rhythmic beating of the heart.…”
Section: Homam-cldh Is a Potent Modulator Of Cardiac Outputmentioning
confidence: 69%
“…Mercier and Russenes, 1992;Wilkens et al, 2005;Cruz-Bermúdez et al, 2006;Cruz-Bermúdez and Marder, 2007;Dickinson et al, 2007;Fort et al, 2007a;Fort et al, 2007b;Christie et al, 2008b;Dickinson et al, 2009). As described earlier, one H. americanus tissue in which CLDH message was detected is the CG, which controls the rhythmic beating of the heart.…”
Section: Homam-cldh Is a Potent Modulator Of Cardiac Outputmentioning
confidence: 69%
“…Previous studies of modulation of the crustacean cardiac neuromuscular system have identified a number of potential sites at which transmitters and hormones can alter output of the system as a whole, and have shown that single modulators often affect multiple sites. Modulators act on the pattern generator of the CG itself (Cruz-Bermudez et al, 2006;Cruz-Bermudez and Marder, 2007;Fort et al, 2004;Fort et al, 2007a;Fort et al, 2007b;Freschi, 1989;Krajniak, 1991;Krajniak et al, 1990;Mercier et al, 2003;Miller and Sullivan, 1981;Saver et al, 1999;Stevens et al, 2008;Stevens et al, 2009). Several of these same modulators, including proctolin (Wilkens et al, 2005), and a number of different FMRFamide-like peptides (Fort et al, 2007a;Stevens et al, 2009;Wilkens et al, 2005), also exert effects at the neuromuscular junction or directly on crustacean cardiac muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory effects of all three AST types (A-, B-and C-types) have been documented in the pyloric pattern generator of the stomatogastric system, but details of the mechanisms used to cause the observed decreases in cycle frequency have not yet been examined Dircksen et al, 1999;Fu et al, 2007;Ma et al, 2009;Szabo et al, 2011). Additionally, inhibitory effects of A-type allatostatins have been recorded in the crab CG (Cruz-Bermudez and Marder, 2007). In this case, cycle frequency decreases as it does in the presence of C-AST in the lobster; however, although it does not change the membrane potentials of motor neurons, A-AST causes a decrease in both the frequency and number of spikes per burst, changes that do not take place in response to C-AST.…”
Section: Discussionmentioning
confidence: 99%
“…preparations with high heart rates, it increases frequency in at least some preparations, notably those in which initial heart rate is very low, and it increases amplitude in virtually all preparations. One notable difference between the experiments reported here and those described in Cruz-Bermúdez and Marder (Cruz-Bermúdez and Marder, 2007) is that our experiments used whole hearts, whereas the effects of AST-B on Cancer were tested on the isolated cardiac ganglion. Thus, it is possible that the excitatory effects of SYWKQCAFNAVSCFamide require feedback from heart muscle tissue.…”
Section: A Physiological Role For Sywkqcafnavscfamidementioning
confidence: 90%
“…cockroaches, crickets and termites (Stay and Tobe, 2007). A-type peptides have also been found in a number of crustaceans (Duve et al, 1997;Dircksen et al, 1999;Duve et al, 2002;Huybrechts et al, 2003;Fu et al, 2005;Yasuda-Kamatani and Yasuda, 2006;Yin et al, 2006;Christie et al, 2008a;Ma et al, 2008;Gard et al, 2009;Ma et al, 2009), where they have been shown to function as locally released and/or hormonally delivered neuro/myomodulators (Skiebe and Schneider, 1994;Jorge-Rivera and Marder, 1997;Jorge-Rivera et al, 1998;Dircksen et al, 1999;Kreissl et al, 1999;Birmingham et al, 2003;Billimoria et al, 2006;Cruz-Bermúdez and Marder, 2007). Molecular, biochemical and mass spectral analyses have shown that multiple isoforms of A-type peptides are common in both insect and crustacean species, with multiple peptides encoded by the known arthropod A-AST prepro-hormones (e.g.…”
Section: Introductionmentioning
confidence: 99%